Evaluating the Effectiveness of the Leadership Pipeline Model in Developing Healthcare Executives and Future Leaders - Ganesan, Dr.Arasuraja; Murugan , Dr.P. SundaraBala; John , Dr.E.P.; John , Dr. Byju; Soni , Dr. Sandeep (International Journal of Accounting and Economics Studies, 2025)
Leadership development is a critical factor in ensuring the long-term sustainability and efficiency of healthcare organizations. The Leadership Pipeline Model (LPM) provides a structured framework for transitioning individuals across various leadership levels, from frontline supervisors to senior executives. This study evaluates the effectiveness of LPM in healthcare settings by examining its impact on leadership competency development, career progression, and organizational performance. Using a mixed-methods approach, quantitative surveys and qualitative interviews were conducted with healthcare executives, mid-level managers, and frontline leaders to assess the practical implementation and challenges of LPM. The study also incorporates case analyses of hospitals that have adopted LPM, identifying key success factors and limitations. Findings suggest that structured leadership progression enhances workforce engagement, succession planning, and overall healthcare service quality. Although, factors like insufficient training support, misalignment with expertise in clinics as well as resistance to variation can increase challenges during the phase of implementation. The conclusion of our study discusses approaches for LPM optimization for the development of leadership in healthcare industries to acquire future leaders who are both adaptive and capable.
Keywords: Healthcare Leadership; Leadership Pipeline Model; Leadership Development; Succession Planning; Executive Training; Healthcare Management; Leader-ship Competency; Organizational Performance; Leadership Transition; Talent Development.